Parasthesia associated with a dentigerous cyst - Escoto, Elmer Jesus T.; Cruz, Eleanor Vera.
Dentigerous cysts are among the common cystic lesions of the oral cavity. Most commonly associated with impacted teeth. Since there is pressure built up within lesion, there is local bone destruction and the possibility of compression on the Inferior Alveolar Nerve, thus causing parasthesia to the ipsilateral side of the jaw. Having performed marsupialization, thereby relieving the pressure, the lesion has decreased in size and compression on the IAN relieved thus retrurning sensation to the areas innervated by the IAN.
Keywords: Dentigerous cyst; Oral cavities